Faith in Frames: Constructing a Digital Game-Based Learning Framework for Religious Education - Papakostas, Christos (Teaching theology and religion, 2024)
This paper discusses the potential of DGBL to facilitate transformation in the context of religious education, arguing for the fact that it is immersive, interactive, and experiential. The paper outlines how this could substantially provide a more engaging learning environment for students, develop critical thinking, and ensure effective learning outcomes. This study explores the advantages and challenges involved in integrating DGBL into curricula for religious education in regard to the alignment between digital game design and pedagogical objectives. These are the important discussions of the application of methodologies in education, constructivist and experiential learning theories, and incorporation of cognitive load optimization strategies to ensure that DGBL does not just enchant students with games but fosters deep understanding of religiously related concepts. Of importance is sharing information to ensure that the content of digital games correctly exemplifies the various traditions of religion and student identity to foster belongingness and respect towards cultural diversity. This paper also takes on board some of the pragmatic issues, among which are professional development by teachers, game design challenges, and possible resistance from other stakeholders who are concerned by the perceived risks associated with gaming. This paper argues that the strategic use of DGBL as a methodology will permit educators to design personalized, engaging, and culturally sensitive learning contexts that enhance students' understanding of and engagement with religious teachings, thus working towards a framework of more inclusive religious education.